Participating doctors’ perspectives on the regulation of voluntary assisted dying in Victoria: a qualitative study - Willmott, Lindy; White, Ben P; Sellars, Marcus; Yates, Patsy M (Medical journal of Australia, 2021)
Objectives To investigate the perspectives of doctors involved with voluntary assisted dying in Victoria regarding the Voluntary Assisted Dying Act 2017 (Vic) and its operation. Design, setting, participants Qualitative study; semi‐structured interviews with 32 doctors who had participated in the voluntary assisted dying system during its first year of operation (commenced 19 June 2019). Doctors were interviewed during April‒July 2020. Results Three major themes related to problems during the first year of operation of the Act were identified: the statutory prohibition of health professionals initiating discussions with their patients about voluntary assisted dying; the Department of Health and Human Services guidance requirement that all doctor‒patient, doctor‒pharmacist, and pharmacist‒patient interactions be face‐to‐face; and aspects of implementation, including problems with the voluntary assisted dying online portal, obtaining documentary evidence to establish eligibility, and inadequate resourcing of the Statewide Pharmacy Service. Conclusions Doctors reported only limited concerns about the Victorian voluntary assisted dying legislation, but have had some problems with its operation, including implications for the accessibility of voluntary assisted dying to eligible patients. While legislative change may resolve some of these concerns, most can be ameliorated by improving the processes and systems.